TRANSFORMASI PENDIDIKAN ISLAM MELALUI KURIKULUM DAN PEMBELAJARAN INOVATIF - Maheswari, M.Pd; Prof. Dr. Herwina, MA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic education is currently confronting the challenges of digital disruption and globalization, demanding internal reforms without eroding Islamic values. This paper aims to analyze the dynamics of implementing the Kurikulum Merdeka (Independent Curriculum) within madrasahs and pesantren (Islamic boarding schools), map out innovative Learning Model frameworks for Islamic Religious Education (PAI), explain the concept of Assessment for Learning (AfL) and authentic evaluation, and formulate strategies for integrating Islamic values into the sciences and social-humanities to dismantle the scientific dichotomy. The study employs a theoretical review and conceptual discussion by referencing current regulations and ideas from prominent Islamic educational thinkers. The findings indicate that madrasahs and pesantren have successfully adopted the Kurikulum Merdeka in an accommodative and autonomous manner, notably through the Project for Strengthening the Pancasila Student Profile and the Rahmatan Lil 'Alamin Student Profile (P5RA). Despite facing obstacles such as human resource readiness, infrastructure limitations, and administrative dualism, this curriculum offers significant opportunities for institutional rebranding. To stimulate student engagement, the application of Project-Based Learning (PjBL) has proven effective in triggering creativity for real-world products, Problem-Based Learning (PBL) sharpens contemporary problem-solving skills, and Research-Based Learning (RBL) enhances data-driven scientific objectivity. Regarding assessment, the integration of AfL and authentic evaluation holistically (kaffah) captures student competency development across affective, cognitive, and psychomotor domains, aligning with the principles of muhasabah (self-reflection) and itqan (thoroughness/excellence). Furthermore, the scientific dichotomy is successfully dismantled through an interconnective approach, where science is positioned as the manifestation of ayat kauniyah (laws of nature/sunnatullah) and the social-humanities are integrated with an Islamic ethical compass.